(untitled) (Bangladesh Journal of Psychiatry, 2022)
Psychiatric disorders have become a global public health concern with its increasing global disease burden. Non-adherence to psychotropic medication has huge grave consequences for both patients and the overall health care system. However, there is paucity of studies on medication non-adherence in the underdeveloped world. The Objective of the study was to identify the factors associated with non-adherence to psychotropic medication among adult patients with major psychiatric disorders. This was a cross sectional study, conducted at National Institute of Mental Health (NIMH), Sher-E-Bangla Nagar, Dhaka, Bangladesh over the period of 12 months from January 2018 to December 2018. For this purpose, 120 adult patients with the age range of 19-65 years, who had history of non-adherence to psychotropic medications, were selected by convenient sampling method. A semi-structured, self-designed questionnaire containing socio-demographic and clinical variables as well as items related to the factors for non-adherence to psychotropic medication was used for data collection. Data was analysed by using statistical package for social sciences (SPSS) 16. The results showed that, among 120 patients, 58.3% were male and 41.7% were female. Age, education, employment status, religion, major psychiatric diseases were significantly associated with factors related to non-adherence to psychotropic medication. Non-adherence to psychotropic medication increases the risk of psychiatric morbidity, mortality and quality of life. So, broad-based efforts must be taken to curb this trend. Bang J Psychiatry 2022;36(2): 24-26